The Expansion of the Subject: Ширење на субјектот - Koteska, Jasna; Ruskovska, Rodna (Identities: Journal for Politics, Gender and Culture, 2005)
Author(s): Jasna Koteska | Јасна Котеска Title (English): The Expansion of the Subject Title (Macedonian): Ширење на субјектот Translated by (Macedonian to English): Rodna Ruskovska | Родна Русковска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 179-200 Page Count: 22 Citation (English): Jasna Koteska, “The Expansion of the Subject,” translated from the Macedonian by Rodna Ruskovska, Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005): 179-200. Citation (Macedonian): Јасна Котеска, „Ширење на субјектот“, Идентитети: списание за политика, род и култура, т. 4, бр. 1-2 (лето - зима 2005): 179-200.